(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2013)
This paper aims to shed light on the findings of the digging process of the water disposal system of the area of Terme Centrali in Nora carried out between 2008 and 2012. The analysis based on the study of the constructive technique, on materials and stratigraphic reports requires further actions to clarify life stages of the sewage pipe, which has been dated to the II-III century AD and considered as an inferior sewer in regard to the baths and to the area itself.